How far are Portuguese prisons inefficient? A non-parametric approach - Marques, Rui
In Portugal, as worldwide, especially in the past decades, crime has become an issue of increasing interest both for society and researchers. The global growth of criminality had several repercussions in the prison system. The most direct one was the overcrowding of prisons. This situation required a great amount of investment to increase the capacity of Portuguese prisons. Simultaneously, the value for money associated with the prisons’ budget has turned itself more and more relevant. These circumstances together emphasize the importance of assessing the prisons’ performance. This study measures the efficiency of Portuguese prison facilities by means of the non-parametric benchmarking approach of data envelopment analysis (DEA). However, due to the limitations of this technique, a bootstrap methodology is also applied in order to add more robustness to the results. Furthermore, a recent procedure is computed to evaluate congestion. The results show relevant levels of inefficiency in the Portuguese prison facilities, which represent an excess of several millions of Euros spent inadequately in this sector.Bootstrap; Congestion; DEA; Efficiency; Portugal; Prison facilities